Reforming Islamic Education in Iran: Creating An Emancipated and Creative Generation - Sulthon Fathoni (SYAMIL: Journal of Islamic Education, 2022)
This research focuses on the theme of Islamic education reform in Iran, which aims to produce an emancipated and creative generation. The Islamic Republic of Iran has implemented a series of education reforms that prioritize the development of technical and vocational skills, entrepreneurship, interpersonal skills, and the cultivation of students' character and morality. The goal of these programs is to prepare students to face the challenges of the global job market and to advance the Iranian economy. Moreover, the Iranian government has introduced a series of initiatives to promote critical thinking and creativity in its education system. For instance, it has integrated modern technology into its educational system, established research centers and incubators, and encouraged student participation in extracurricular activities. As a result of these reforms, many Iranian students have emerged as successful graduates in various fields, including technology, science, business, and arts. Therefore, this abstract concludes that the Islamic education reform in Iran has been successful in creating a generation of students who are equipped with the skills and knowledge necessary to compete in the global job market and contribute to the advancement of their country's economy. Furthermore, it has also fostered a culture of critical thinking, creativity, and innovation among students, which will be critical to the country's continued progress in the future.